Exploring the consistency of the SF-6Dv2 in a breast cancer population. (3rd September 2021) - Ameri, Hosein; Safari, Hossein; Poder, Thomas
ABSTRACT: Background : Short-Form Six-Dimension version 2 (SF-6Dv2) is a multi-attribute utility instrument that can be used in combination with the SF-36v2 (SF-6Dv2SF-36 ) or as an independent instrument in two forms: six questions (SF-6Dv2ind-6 ) and 10 questions (SF-6Dv2ind-10 ). The purpose of this research was to assess the consistency between the results of the SF-6Dv2ind-6 and the SF-6Dv2SF-36 in patients with breast cancer. Research design and methods : This cross-sectional study was carried out on 418 patients with breast cancer. The degree of agreement between the descriptive systems of instruments was calculated using Spearman's correlation coefficient, global consistency index (GCI), and identically classified index (ICI). Results : The average size of the Spearman's correlation coefficients between the descriptive systems of instruments was higher than 0.5. The results of the GCI revealed that the level of agreement between dimensions of the two instruments had a mean of 64.9 (range 32.45–86.8). The SF-6Dv2SF-36 generates statistically higher values than does the SF-6Dv2ind-6, and mean difference between the two instruments was 0.087 for model 3 and 0.027 for model 10. Conclusions : This study provided evidence that the SF-6Dv2SF-36 and the SF-6Dv2ind-6 may produce different answers from patients with breast cancer and lead to a small difference in utility values.